Hyperthyroidism in childhood: peculiarities of the different clinical pictures - Zirilli, Giuseppina; Velletri, Maria Rosa; Porcaro, Federica; Di Giovine, Giuseppina; Maisano, Pina; La Monica, Giuseppina (Acta Biomedica Atenei Parmensis, 2015)
Background: clinical and biochemical picture of hyperthyroidism in children may significantly change according to its etiologies. Objectives: to report the most recent views about epidemiology, pathophysiology, clinical and biochemical course, diagnostic procedures and management of hyperthyroid syndrome in childhood, according to its different etiologies. Design: Graves’ disease and Hashimoto’s thyroiditis are responsible for 84% and 12%, respectively, of all the cases of hyperthyroidism in childhood. Hyperfunctioning thyroid nodules (<3% of cases), TSH-secreting adenomas ( 1%) and McCune-Albright syndrome ( 1%) are distinctly less common. The main hormonal and immunological features of all these conditions were summarizes in Table1, whereas their anamnestic and clinical peculiarities and the diagnostic procedures which may be useful in the differential diagnosis were reported in Table 2. Conclusions: 1) hyperthyroid syndrome in childhood may present with very different clinical pictures, which are specifically related to the respective etiologies; 2) diagnostic procedures and therapeutic management are not the same in the various conditions.